A rare whistling foreign body bronchus - Budhiraja, Grace; Singh, Harsimrat; Harpreet; Prabhjot; Goyal, Nischai (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
A case of toy-whistle as foreign body (FB) initially presented in sub-glottic location and later on got transferred to right segmental bronchus after induction of anaesthesia, is discussed. The FB was removed by rigid bronchoscopy. This case is illustrative of the problem inherent in removal of FB from air passages in children. The relevant literature has been reviewed.